2011
DOI: 10.1136/heartjnl-2011-300130
|View full text |Cite
|
Sign up to set email alerts
|

Case fatality rates for South Asian and Caucasian patients show no difference 2.5 years after percutaneous coronary intervention

Abstract: In this large PCI cohort, the in-hospital and longer-term mortality of South Asians appeared no worse than that of Caucasians. South Asians had higher rates of restenosis and CABG during follow-up. Data suggest that the excess coronary mortality for South Asians compared with Caucasians is not explained by differences in case-fatality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
6
12
0
Order By: Relevance
“…Bhopal, Scottish Health and Ethnicity Linkage Study). Using a similar study design with routinely collected hospital administrative data linked to cardiac procedure registries from British Columbia and the Calgary health region area in Alberta, Canada, Khan et al 14 reported that south Asian patients had a lower relative risk of long-term mortality compared with white patients (hazard ratio 0.65; 95% CI 0.57 to 0.72), while in-hospital and longer-term mortality of south Asians appeared no worse than that of Caucasians in a study of 9771 patients who underwent percutaneous coronary intervention in a London teaching hospital serving a large south Asian community (18.5% were south Asian, with diabetes being far more prevalent in south Asians at 45.9±1.2% vs 15.7±0.4%, p<0.0001 in Caucasians) 15. These new studies have contradicted some earlier reports, but it looks like the outcome after presentation with coronary disease is not worse in south Asians in spite of their high prevalence of diabetes.…”
Section: Is the High Rate Of Coronary Mortality In South Asians A Resmentioning
confidence: 95%
“…Bhopal, Scottish Health and Ethnicity Linkage Study). Using a similar study design with routinely collected hospital administrative data linked to cardiac procedure registries from British Columbia and the Calgary health region area in Alberta, Canada, Khan et al 14 reported that south Asian patients had a lower relative risk of long-term mortality compared with white patients (hazard ratio 0.65; 95% CI 0.57 to 0.72), while in-hospital and longer-term mortality of south Asians appeared no worse than that of Caucasians in a study of 9771 patients who underwent percutaneous coronary intervention in a London teaching hospital serving a large south Asian community (18.5% were south Asian, with diabetes being far more prevalent in south Asians at 45.9±1.2% vs 15.7±0.4%, p<0.0001 in Caucasians) 15. These new studies have contradicted some earlier reports, but it looks like the outcome after presentation with coronary disease is not worse in south Asians in spite of their high prevalence of diabetes.…”
Section: Is the High Rate Of Coronary Mortality In South Asians A Resmentioning
confidence: 95%
“…7,27,55-57 However, short-7-9,27,32,55,58 and long-term mortality 7,27,31,32,34,51 after MI appeared to be similar among South Asian and white people (Appendix 3).…”
Section: Diagnosis Management and Outcomesmentioning
confidence: 97%
“…were more likely to have hypertension compared with white people 3,4,9,14,27,28,31,32,[34][35][36]41,44 (OR 1.11, 95% CI 1.02 to 1.22, p = 0.02).…”
Section: Cmaj Openmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have suggested higher case-fatality rates following acute myocardial infarction (AMI) in migrant SA patients compared with White European (WE) patients in the UK,9 10 others from the UK5 11–13 and Canada8 14 have suggested similar11 12 14 15 or better5 8 13 adjusted survival for these ethnic groups in this setting.…”
Section: Introductionmentioning
confidence: 99%